Mengurangi Kecemasan Berbicara di Kalangan Siswa EFL Melalui Dola AI: Meningkatkan Kemampuan Berbicara Lisan - Lidia Permatasari Siagian; Adib Jasni Kharisma; Diani Syahputri (Journal of Social, Humanity, and Education, 2026)
Purpose: This study explores the role of DOLA AI–mediated speaking practice in reducing speaking anxiety and improving oral proficiency among Grade XII English as a Foreign Language learners in Thailand. Speaking anxiety is a major barrier that affects fluency, confidence, and willingness to communicate in classroom settings. Research Methodology: This study used a descriptive qualitative design. Grade 12 students with high levels of speaking anxiety were purposively selected. Data were collected through classroom observations, semi-structured interviews, and AI interaction logs. Miles, Huberman, and Saldaña’s interactive model was applied for data analysis, including reduction, display, and conclusion drawing. Results: AI-mediated speaking practice significantly reduced anxiety-related behaviors, such as hesitation and avoidance. Learners spoke more, participated voluntarily, and showed increased confidence in pronunciation. Interviews revealed that students experienced reduced fear of negative evaluation and felt more emotionally comfortable with DOLA AI than with traditional classroom activities. Conclusions: DOLA AI acts as an affective-supportive partner that reduces learners’ affective filters and builds communicative confidence in EFL speaking practice. Limitations: The study had a small sample size from a limited context, affecting its generalizability. The short observation period did not capture long-term language development, and AI interaction logs may not fully reflect learners’ emotional states or classroom dynamics. Contributions: This study provides evidence of the affective benefits of AI-assisted speaking practice, particularly in Southeast Asian EFL contexts, and offers insights for integrating AI into anxiety-sensitive language learning environments.